Characterization and anticorrosive properties of poly(2, 3‐dimethylaniline)/nano‐Al2O3 composite synthesized by emulsion polymerization. (18th June 2013) - Li, Zhitao; Ma, Li; Li, Wanglin; Gan, Mengyu; Qiu, Wei; Yan, Jun
Abstract : Poly(2, 3‐dimethylaniline)/nano‐Al2 O3 composite (PAC) was synthesized by emulsion polymerization using dodecyl benzene sulfonic acid as emulsifier and dopant. The structure of PAC was characterized by Fourier fransformation infrared spectroscopy, UV–visible adsorption spectroscopy, and field emission scanning electron microscopy. The thermal stability was studied by thermogravimetric analysis, and the electrochemical performances were studied by cyclic voltammetry measurements. Epoxy coatings containing PAC and poly(2, 3‐dimethylaniline) (P(2, 3‐DMA)), respectively, were painted on steel, and accelerated immersion tests were performed to evaluate the anticorrosion property of the coatings in 3.5% NaCl solution. The results showed that the addition of PAC and P(2, 3‐DMA) could improve the anticorrosion performance of epoxy coating significantly and the PAC coating had higher corrosion resistance than that of P(2, 3‐DMA). Copyright © 2013 John Wiley & Sons, Ltd.